2020
DOI: 10.21203/rs.3.rs-26657/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age associated level of estradiol (E2) and progesterone (4) influence IL-8 response to Mycobacterium tuberculosis (Mtb) antigens in women.

Abstract: Tuberculosis (TB) is an intracellular infection controlled the effective recruitment of effectors immune cells at infection site. In aged premenopausal or menopausal women, there is an increased pro-inflammatory cytokines secretion suggesting an underlying link between cytokines response and estrogen (E2) and progesterone (P4) levels. In this study we compared women aged 40 years old and above (premenopausal) and women aged below 40 years old with and without latent TB infection to determine the link between E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, it has been reported that E2 and P4 exhibit both proinflammatory and anti-inflammatory responses in a dose-and context-dependent manner [14] [15] [16] [17]. In this study for which a preliminary version has been released as a pre-print at Research Square [18], we investigated the relationship between E2, P4 and cytokines response to Mtb-antigens in women.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that E2 and P4 exhibit both proinflammatory and anti-inflammatory responses in a dose-and context-dependent manner [14] [15] [16] [17]. In this study for which a preliminary version has been released as a pre-print at Research Square [18], we investigated the relationship between E2, P4 and cytokines response to Mtb-antigens in women.…”
Section: Introductionmentioning
confidence: 99%